LITERATURE REVIEW: PUBLIC PERCEPTIONS OF THE ROLE OF PHARMACISTS IN PHARMACIES - Agustin, HESTI; Salsabila, Kansha Aulia; Nisa, Laelatul; Padila, Nisa; Latiefah, Asri Dewi (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
The role of pharmacists in community pharmacies is evolving from product-oriented to pharmaceutical care. However, the success of this role expansion is greatly influenced by public perception, expectations, and trust in pharmacists. Objective: This literature review aims to examine public perception of the role of pharmacists in pharmacies and summarize the factors that influence it as a basis for strengthening the quality of pharmaceutical services. Method: The study used a literature review design. Articles were searched through PubMed, ScienceDirect, MDPI, and Google Scholar using keywords related to public/patient perceptions of the role of pharmacists in pharmacies. Articles were screened based on inclusion-exclusion criteria, duplicates were removed, then data extraction (author/year, location, design, sample, instrument, findings) and thematic narrative synthesis were performed. Results: In general, public perception of the role of pharmacists tends to be quite good, especially in prescribing services and providing drug information. However, understanding of the clinical role of pharmacists (comprehensive counseling and therapy monitoring) is still not optimal, so that the role of pharmacists is often perceived as limited to drug dispensing. Cross-country studies show that public perception is generally positive towards pharmacist competence, but the level of public trust in pharmacists as drug therapy consultants is relatively lower than that of doctors. Educational factors, interaction experience, and communication quality influence perception and trust. Conclusion: Public perception of pharmacists in pharmacies is relatively good, but traditional roles are still dominant. Strengthening the clinical role requires more consistent counseling, pharmacist visibility in service areas, and public education on the benefits of comprehensive pharmaceutical services. Keywords: public perception; pharmacist; community pharmacy; pharmaceutical services; pharmaceutical care.